Knowledge transfer: a worldwide challenge in child mental health: a recommendation to the readership of CAPMH concerning the revised version of the IACAPAP Textbook of Child and Adolescent Mental Health - Anna T. Maier; Rebecca C. Brown; Joerg M. Fegert (BMC, 2018)
Abstract Background Transfer of knowledge is an important issue throughout all scientific disciplines, especially in the medical and psycho-social field. The issue of worldwide knowledge transfer in child mental health is one of the aims and goals of the journal Child and Adolescent Psychiatry and Mental Health (CAPMH). The demand for mental health training is high worldwide, and especially in low- to lower-middle income countries, where inadequate access to knowledge resources in the field of child and adolescent mental health (CAMH) is prevalent. At the same time, many of these countries are showing an increased risk for mental health issues in children and adolescents. The International Association for Child and Adolescent Psychiatry and Allied Professions (IACAPAP) Textbook of Child and Adolescent Mental Health counters this problem. It is an open-access e-textbook aiming to provide an overview of current and established treatment and practical approaches for child and adolescent psychiatrists, psychotherapists and allied (mental health) professionals worldwide. First published in 2012, the updated and revised version was launched in 2015. The aim of this commentary is to review and disseminate the usefulness and practicability of content and further material included in the new version of the textbook. Review Overall, the textbook contains ten sections divided into 59 chapters, with a total of 1435 pages. The original version of the textbook was written in English. The revised version contains translations of 49 chapters into different languages (to date French, Spanish, Hebrew, Arabic, Portuguese, Russian, Norwegian and/or Japanese), with additional material for knowledge dissemination and self-directed learning (e.g. videos and quizzes) for several chapters. The textbook and the add-on materials for dissemination are of high quality and convey a great introduction to important topics concerning mental health. Apart from knowledge transfer, there is a pragmatic focus on clinical practice and on regional and cultural differences. Conclusion The textbook is a new and unique opportunity for professionals all over the world to improve their knowledge, skills and expertise in CAMH. High-quality, up-to-date and freely accessible materials in the field of CAMH are combined with the opportunity to share insights with colleagues.